2004
DOI: 10.1007/s00106-003-0964-1
|View full text |Cite
|
Sign up to set email alerts
|

Submillimetrische 3D-Navigation im Felsenbein

Abstract: These results show that intraoperative 3-D navigation can be successfully transferred to a clinical application in the petrous bone or at the cerebellopontine angle with satisfactory accuracy in this highly sensitive anatomic region, even if only a restricted area of the patient can be used for the referencing procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(18 reference statements)
0
6
0
1
Order By: Relevance
“…Hier werden die pr ä operativen Daten mit der Patientenanatomie zur Deckung gebracht. Haupts ä chlich kommen [8,9 ], bei hochaufl ö senden Datens ä tzen der lateralen Sch ä delbasis ist die radiologisch dargestellte Oberfl ä che sehr klein ist und bietet kaum eindeutige Konturen. Hier kommt ü blicherweise die Punkt-zu-Punkt Registrierung anhand von zuvor implantierten Titanschrauben zur Anwendung [10,11] .…”
Section: Lernkurve Bei Der Registrierung Navigierter Eingriff E An Deunclassified
“…Hier werden die pr ä operativen Daten mit der Patientenanatomie zur Deckung gebracht. Haupts ä chlich kommen [8,9 ], bei hochaufl ö senden Datens ä tzen der lateralen Sch ä delbasis ist die radiologisch dargestellte Oberfl ä che sehr klein ist und bietet kaum eindeutige Konturen. Hier kommt ü blicherweise die Punkt-zu-Punkt Registrierung anhand von zuvor implantierten Titanschrauben zur Anwendung [10,11] .…”
Section: Lernkurve Bei Der Registrierung Navigierter Eingriff E An Deunclassified
“…The registration accuracy was similar to the implanted screws and superior to surface registration. 15 Different modalities of radiological imaging have been used for navigation, mainly multislice computed tomography (MSCT), 1,[7][8][9][13][14][15]18 but also flat panel computed tomography (fpCT) 17 and flat panel volume computed tomography (fpVCT). 10 A fpVCT system has an innovative design that allows higher spatial resolution for the visualization of complex human anatomy in comparison to MSCT scanners.…”
Section: Introductionmentioning
confidence: 99%
“…2 Different navigation systems have been used at the lateral skull base, like electromechanical systems, [3][4][5] electromagnetic systems [6][7][8][9][10][11][12] or optical systems. 1,7,[13][14][15][16][17][18] In some studies, the precision of these navigation modalities was specifically compared. Ecke et al 7 reported that different optical systems varied considerably in the accuracy between laboratory and clinic, whereas the electromagnetic system showed similar results in both settings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations